Frequent CEO Turnover and Firm Performance: The Resilience Effect of Workforce Diversity - Kim, Youngsang; Jeong, Sophia Soyoung; Yiu, Daphne W.; Moon, Jinhee (Journal of business ethics, 2021)
CEO turnover (or succession) is a critical event in an organization that influences organizational processes and performance. The objective of this study is to investigate whether workforce diversity (i.e., age, gender, and education-level diversity) might have a resilience effect on firm performance under the frequency of CEO turnover. Based on a sample of 409 Korean firms from 2010 to 2015, our results show that firms with more frequent CEO turnover have a lower firm performance. However, firms with more gender and education-level diversity could buffer the disruptive effect of frequent CEO turnover on firm performance to offer a benefit to the organization. Our theory and findings suggest that effectively managing diverse workforce can be a resilience factor in an uncertain organizational environment because diverse workforce has complementary skills and behaviors that can cope better with uncertainty and signals social inclusion of an organization, thus fostering a long-term exchange relationship. These findings contribute to the literature on CEO turnover (or succession) and diversity.